KEANEKARAGAMAN JENIS SEMUT (Formicidae) ARBOREAL DI HUTAN MANGROVE KELURAHAN SETAPUK BESAR KOTA SINGKAWANG - Mazlan, .; Kartikawati, Siti Masitoh; Burhanuddin, . (JURNAL HUTAN LESTARI, 2019)
Arboreal ants are ants that do activities and spend their lives in tree. Roles of this organism are to serve as decomposers, pollinators, predators and indicators. Ant species diversity constitutes a chain for ecosystem stability. They are responsible as decomposing insects making their presence becomes ecologically vital. Research on ant species diversity in mangrove forest remains insufficient. One of the reasons possibly is that fact that mangrove is an ecosystem which is affected by sea tide. This research aims at gathering data about ant species diversity based on types of mangrove forest vegetation located in Setapuk Besar, Singkawang City. The research used a survey method by observing types of trees whose diameter was 10 cm and above. Additionally, the tree should have a large number of ants. The data was collected through fly sheet trap set under, in the mid, and above the tidal level. Findings revealed 6 types of ants consisting 4 sub-families in 6 types of the trees i.e. Rhizopora mucronata, Avicennia lanata, Hibiscus tiliaceus, Terminalia capatta, Nypa fruticans, and Bruguiera cylindrical.. Based on the diversity index of those 6 types of trees, the divercity of arboreal ants spesies could be categorized low (H’<1). The highest diversity was nypa fruticans vegetation by 0.325. This was because the tree contains sugar level and carbohydrate. The lowest diversity was Hibiscus tiliaceus and Termialia catappa. The H’ value was 0. One of the reasons was because only one species of ants can be found in both trees, namely Oecophylla smaragdina.Keywords: Arboreal Ants, Diversity, Mangrove, Singkawang